Metamaterial-based injection molding for the cost-effective production of whole cuts - Mohammad Ghosheh; Avner Ehrlich; Amit Fischer; Laura Pasitka; Merav Cohen; Yaakov Nahmias (Nature Communications)
Abstract The escalating global demand for meat products has intensified ecological concerns, underscoring the need for sustainable meat alternatives. Although current methods effectively imitate ground meat, mimicking whole cuts, which constitute 54% of the global market, remains challenging due to the lack of scalable technology. Injection molding is a massively scalable manufacturing technology developed for the polymer industry. Here, we introduce two injectable metamaterials: a thermally irreversible fat composite we named proteoleogel, and a multi-scaled meat analog produced by low-temperature extrusion. Viscoelastic screening of plant proteins identifies mung bean for its ability to stabilize complex oleogel structures, mimicking the mechanics of adipose tissue. Mechanical analysis reveals that low-temperature extrusion produces microscale isotropic fibers and mesoscale anisotropic structures mimicking muscle and fascia. These metamaterials can be injection-molded into various whole cuts, from chops to T-bones. Blinded taste tests indicate a 43% preference for our plant-based steak analog. Moreover, technical economic analysis shows injection molding is more cost-effective than 3D printing, costing $9/kg compared to $38/kg. This research represents a step in sustainable food production, offering cost-effective and scalable solutions for the entire meat market.